Effect of Coercive Voltage and Charge Injection on Performance of a Ferroelectric-Gate Thin-Film Transistor - P. T. Tue; T. Miyasako; E. Tokumitsu; T. Shimoda (Advances in Materials Science and Engineering)
We adopted a lanthanum oxide capping layer between semiconducting channel and insulator layers for fabrication of a ferroelectric-gate thin-film transistor memory (FGT) which uses solution-processed indium-tin-oxide (ITO) and lead-zirconium-titanate (PZT) film as a channel layer and a gate insulator, respectively. Good transistor characteristics such as a high “on/off” current ratio, high channel mobility, and a large memory window of 108, 15.0 cm2 V−1 s−1, and 3.5 V were obtained, respectively. Further, a correlation between effective coercive voltage, charge injection effect, and FGT’s memory window was investigated. It is found that the charge injection from the channel to the insulator layer, which occurs at a high electric field, dramatically influences the memory window. The memory window’s enhancement can be explained by a dual effect of the capping layer: (1) a reduction of the charge injection and (2) an increase of effective coercive voltage dropped on the insulator.